Non‐Aqueous Primary Li–Air Flow Battery and Optimization of its Cathode through Experiment and Modeling. Issue 21 (24th October 2017) - Kim, Byoungsu; Takechi, Kensuke; Ma, Sichao; Verma, Sumit; Fu, Shiqi; Desai, Amit; Pawate, Ashtamurthy S.; Mizuno, Fuminori; Kenis, Paul J. A.
Abstract: A primary Li–air battery has been developed with a flowing Li‐ion free ionic liquid as the recyclable electrolyte, boosting power capability by promoting superoxide diffusion and enhancing discharge capacity through separately stored discharge products. Experimental and computational tools are used to analyze the cathode properties, leading to a set of parameters that improve the discharge current density of the non‐aqueous Li–air flow battery. The structure and configuration of the cathode gas diffusion layers (GDLs) are systematically modified by using different levels of hot pressing and the presence or absence of a microporous layer (MPL). These experiments reveal that the use of thinner but denser MPLs is key for performance optimization; indeed, this leads to an improvement in discharge current density. Also, computational results indicate that the extent of electrolyte immersion and porosity of the cathode can be optimized to achieve higher current density. Abstract : Let it flow : A new architecture for a lithium–air (Li–air) battery, a flowing electrolyte system, is proposed for improving discharge capacity as well as current density. Also, experimental and computational investigations on optimizing cathodes specifically for the Li–air flow battery are reported.